2011
DOI: 10.1016/j.jgeb.2011.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of cystatin C and beta-2 microglobulin in preeclampsia

Abstract: The purpose of this study was to determine whether the levels of cystatin C and beta-2 microglobulin (B2M) are altered during the second trimester in the plasma of women who subsequently develop preeclampsia. Study design: We performed a case control study to compare the levels of cystatin C and B2M in women in whom preeclampsia ultimately developed (n = 30) and in pregnant women who remained normotensive throughout gestation (n = 60). The maternal plasma levels of cystatin C and B2M were measured by enzyme-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…A possible predictive value of cystatin C in preeclampsia was highlighted in a recent study by Farag et al (29). The authors showed the significantly elevated levels of cystatin C and beta 2 microglobulin in women who were in the second trimester of pregnancy and subsequently developed preeclampsia compared with healthy pregnant women (29). Oxidative stress and maternal endothelial dysfunction due to placental ischemia might be detected before the onset of PE; thus, combining oxidative stress markers and cystatin C with other markers in early periods of pregnancy to evaluate the predictive value in preeclampsia might be in scope of future studies.…”
Section: Table Demographic Laboratory and Clinical Characteristics mentioning
confidence: 91%
See 1 more Smart Citation
“…A possible predictive value of cystatin C in preeclampsia was highlighted in a recent study by Farag et al (29). The authors showed the significantly elevated levels of cystatin C and beta 2 microglobulin in women who were in the second trimester of pregnancy and subsequently developed preeclampsia compared with healthy pregnant women (29). Oxidative stress and maternal endothelial dysfunction due to placental ischemia might be detected before the onset of PE; thus, combining oxidative stress markers and cystatin C with other markers in early periods of pregnancy to evaluate the predictive value in preeclampsia might be in scope of future studies.…”
Section: Table Demographic Laboratory and Clinical Characteristics mentioning
confidence: 91%
“…Early prediction of PE is imperative for improving the maternal and fetal consequences. A possible predictive value of cystatin C in preeclampsia was highlighted in a recent study by Farag et al (29). The authors showed the significantly elevated levels of cystatin C and beta 2 microglobulin in women who were in the second trimester of pregnancy and subsequently developed preeclampsia compared with healthy pregnant women (29).…”
Section: Table Demographic Laboratory and Clinical Characteristics mentioning
confidence: 98%
“…[24][59][60] [61] Cell-free foetal DNA, p-selectin (before 20 weeks), pentraxin 3 (all trimesters), free foetal Hb F, the antiplasmin alpha 2-microglobulin, cystatin -C and beta-2 microglobulin, maternal serum netrin-I are increased while pregnancy-associated plasma protein A (PAPP-A), placental protein-13…”
Section: The Immune-inflammatory Cascadementioning
confidence: 99%
“…From the above explan-ation, the serum cystatin C has superior diagnostic accuracy as a marker of glomerular endoteliosis or renal involvement in preeclampsia compared to creatin-ine. 4,11,12 Studies conducted Franceschini et al (2008) and Mona Faraq et al (2011) found that cystatin C levels rise higher in patients with preeclampsia compared than in normotensive pregnancy.Helena Strevens et al (2002) compared the levels of cystatin C, creatinine and uric acid. Cystatin C has superior diagnostic accuracy for preeclampsia compared with serum uric acid or creatinine.…”
Section: Introductionmentioning
confidence: 99%
“…Cystatin C has superior diagnostic accuracy for preeclampsia compared with serum uric acid or creatinine. [11][12][13] Incidence of perinatal morbidity and mortality is rising in pregnancy with preeclampsia, and this is mainly due to preterm labor and uteroplacental insufficiency, which results in decreased blood flow to the fetus. Prematurity, fetal growth retardation (IUGR), and fetal death (IUFD) are neonatal complications that should be well-anticipated in patients with preeclampsia.…”
Section: Introductionmentioning
confidence: 99%